Maqashid Syari'ah Index Model in Sharia Bank - Mukminati Ridwan; Gagaring Pagalung; Mukhtar Luthfi; Abd Rauf Muhammad Amin (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: This study aims to develop an appropriate and comprehensive framework for measuring the implementation of Maqashid Syari'ah principles in Sharia banking, particularly amid global economic crises. Methodology: The method used is a qualitative method with a literature approach. The data used are the results of published research using the Maqashid Syari'ah index with the study object of sharia banking. Results: The study found five Maqashid Syari'ah measurement concepts for assessing Sharia bank compliance. These concepts share three main goals such us soul purification, justice, and public welfare, measured through interest-free business, zakat, and real investment. Conclusions: This study concludes that Islamic banking performance should be measured using a Sharia-compliant framework based on the Maqashid Syari'ah Index. The proposed model identifies three main dimensions, namely halal income, zakat, and real investment, which represent purification of the soul, justice, and public welfare. Limitations: This study is limited to a qualitative literature-based analysis and does not conduct empirical testing using financial data from Islamic banks. Therefore, future studies are encouraged to validate the proposed model quantitatively across different Islamic banking institutions. Contributions: This study contributes by synthesizing five